STRATEGIC MANAGEMENT FOR THE SUCCESSFUL DIGITAL TRANSFORMATION OF INDUSTRIAL AUTOMATION COMPANIES - Joshi, Rajeev Ramesh (Digital Repository of Theses, 2023)
The role of information technology has become critical in globalized business and day-to-day life. Digital transformation impacts all segments of industries and the business world, like manufacturing, retail markets, healthcare, real estate, and education. Industrial automation (IA) companies known as pioneers of industry 3.0 are not immune to this new disruption. IA companies are under pressure of twofold transformation: they must undergo internal operation transformation and support their client’s transformation journeys in the manufacturing and process industries. However, digital transformation is complex; many organizations spend millions only to hit roadblocks. This research explores and understands how some organizations successfully implemented digital transformation while others still struggle. The fundamental question is: "What are the factors and strategies for successful implementation?" The researcher has analyzed the data collected through a literature review and interviews with executives and leaders. This research has identified the driving factors, required action fields, and critical success factors of the digital transformation pertaining to industrial automation (IA) companies. The research aim is to formulate a digital transformation strategic management plan for industrial automation (IA) companies. Given the requirement for in-depth insight from the practitioners and leaders, a qualitative method was adopted to collect and analyze the data. Semi-structured interviews with 16 professionals were used for data collection and then analyzed using content analysis for interference and conclusion. Developed strategic management is expected to help IA companies successfully implement digital transformation and sustain its benefits.